Students` Responses in Enhancing New Vocabulary Through Subtitled English Movies - Katemba, Caroline Victorine; Ning, Wei (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2018)
The aims of this study is to find out the student responses in enhancing new vocabulary through subtitled English Movies. And the research question is “what are students` responses in enhancing new vocabulary through subtitled English movies?” to achieve this objective, the study employed a quantitative method. The data were obtained from questionnaire. The questionnaire were distributed to the Universitas Advent Indonesia. The data were then descriptively analyzed. The result of this study indicated that most of student responded positively through subtitled English movies in enhancing new vocabulary. This research findings are expected to contribute to the efforts in the teaching and learning area, particularly in increasing students` vocabulary. Keywords: Subtitled English Movies, Student` Responses, Vocabulary